Penerapan model pembelajaran treffinger untuk meningkatkan kemampuan berpikir kreatif matematis siswa - Rusdian Rifa'i; Asep Sujana; Ira Romdonah (Department of Mathematics Education, UIN Sunan Gunung Djati Bandung, West Java, Indonesia, 2020)
This study aims to determine the improvement of mathematical creative thinking skills of class XI students of Aliyah Mathla’ul Anwar Madrasah Menes Center through the treffinger learning model. This study uses a quasi-experimental method that is nonequivalent pretest-posttest control group design, while the research technique used is purposive sampling where in determining the sample based on certain considerations. The population in this study were all students of class XI of the Aliyah Mathla'ul Anwar Madrasah Menes Center, while the sample used was students of class XI IPA 1 and XI IPA 2 Aliyah Mathla'ul Anwar Madrasah Menes Center. The procedure for collecting data in this study uses the observation and test methods. The instrument used in this study was a test of students' mathematical creative thinking skills in the form of a description test. The data obtained in this study are quantitative data. Quantitative data processing is done through normality test, homogeneity test, average difference test. The statistics used in processing data are parametric statistics with t-test. Based on the results of data processing and hypothesis testing, it was concluded that mathematical creative thinking skills of class XI students of Aliyah Madrasah Mathla'ul Anwar Menes Center who obtained the Treffinger learning model were better than students who obtained conventional learning.